Screening of antimicrobial peptides from hemolymph extract of tasar silkworm Antheraea mylitta against urinary tract and wound infecting multidrug-resistant bacteria - Dutta, Suhrid R.; Gauri, Samiran S.; Mondal, Bikash; Vemula, Abhilash; Haider, Suman Kumar; Mondal, Keshab Chandra; Ghosh, Ananta K. (Acta Biologica Szegediensis, 2016)
Antimicrobial peptides (AMPs) are an evolutionarily conserved component of the innate immune response and they were found among all classes of life forms. In the present study AMPs were extracted from the hemolymph of Antheraea mylitta and fractionated by High Performance Liquid Chromatography (HPLC). Antimicrobial activity was tested against three clinically isolated multidrug-resistant (MDR) bacteria, such as urinary tract infecting Escherichia coli, wound infecting Pseudomonas aeruginosa and Bacillus pumilus. Fraction I (comprised of three different peptides of varying mass) did not inhibit the growth of any of these clinical isolates, whereas, fraction III inhibited the growth of B. pumilus without affecting the growth of gram-negative isolates. Fraction II exhibited bactericidal effects against P. aeruginosa and E. coli, whereas, B. pumilus was not susceptible. Scanning electron microscopic study revealed that serious structural alterations of cell morphology and disruption of the outer membrane, that facilitates the release of cytoplasmic content through holes and channels in E. coli, treated with this isolated peptide. Our results indicate that the peptide from the isolated fraction could be used as potent alternative antimicrobial compounds for the treatment of MDR E. coli andP. aeruginosa infections.